Copyright : interpreting the law for libraries, archives and information services / Graham P. Cornish. - Cornish, G. P. (Facet, 2015)
Cornish's Copyright is the standard work in its field and is indispensable for all librarians and information professionals and who are looking for solutions to their copyright problems. The book explains the provisions of the UK Copyright Act and supporting legislation in quick and easy question-and-answer form. This latest edition is revised and expanded in the light of new legislation which came into force in 2014/5 and some decisions by the courts which have changed our understanding of what the law means. Areas such as moral rights, originality, databases, and the use of broadcast material in education all receive detailed attention, along with Wikipedia, Creative Commons and Open Archives. Copyright is also considered in the context of social media.